Clinical Significance of Neuro-Otological Examinations in Persistent Postural-Perceptual Dizziness: A Retrospective Study - Fumiyuki Goto; Shoji Kaneda; Koichiro Wasano (The Journal of International Advanced Otology, 2026)
BACKGROUND: Persistent postural-perceptual dizziness (PPPD) is a chronic functional vestibular disorder characterized by non-spinning dizziness, postural instability, and hypersensitivity to visual and motion stimuli. While Bárány Society criteria enable diagnosis, the prognostic value of neuro-otological examinations remains unclear. To assess the relationship between neurootological test results and short-term clinical improvement in PPPD, clarifying their clinical significance. METHODS: A retrospective review was conducted of 24 patients with PPPD identified from 103 patients with intractable dizziness treated between 2022 and 2024. All underwent video head impulse testing (vHIT), cervical vestibular-evoked myogenic potential (cVEMP), and ocular VEMP (oVEMP). Semicircular canal dysfunction was defined as reduced gain with corrective saccades; otolith dysfunction as absent responses or abnormal asymmetry ratios. Dizziness Handicap Inventory (DHI) and Hospital Anxiety and Depression Scale (HADS) were administered. All received selective serotonin reuptake inhibitors plus structured vestibular rehabilitation. Clinical improvement was evaluated with the Clinical Global Impression-Improvement (CGI-I) scale at 3 months. RESULTS: Among the 23 patients analyzed, the mean CGI-I score was 2.7 ± 0.9. Ten patients had a good prognosis (mean CGI-I score,1.8 ± 0.4), whereas 13 had a poor prognosis (mean CGI-I score, 3.4 ± 0.5). No significant differences in DHI or HADS scores were observed between the prognosis groups. Otolithic vertigo was the most common precipitating condition. Otolith dysfunction was identified in 9 patients (38%): cVEMP only (n=5), oVEMP only (n=1), and both (n=3). No horizontal semicircular canal dysfunction was detected on vHIT. Prognosis did not differ significantly between patients with (3.1 ± 0.8) and without (2.5 ± 0.9) vestibular dysfunction (P > .05). A history of psychiatric consultation was also not associated with prognosis (P > .05). Patients who initiated treatment within 3 months of symptom onset tended to have better outcomes, although the difference was not statistically significant. CONCLUSION: Over one-third of PPPD patients demonstrated otolith dysfunction, suggesting peripheral vestibular involvement in pathogenesis. While vestibular test abnormalities were not linked to short-term prognosis under standardized therapy, cVEMP and oVEMP provided patho-physiological insights and identified isolated otolith deficits undetected by vHIT. Larger prospective studies are warranted to evaluate their prognostic utility and guide personalized rehabilitation.